PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI SDN 005 SEKOLAQ MULIAQ DI KUTAI BARAT - Elfreda Aplonia Lau, Elvira Widarti, Titin Ruliana, (EKONOMIA, 2016)
The purpose of this thesis is to find out whether the style of leadership and the working environment have a significant effect on the performance of an employee or not at SDN 005 Sekolaq Muliaq in West Kutai. And to find out which of the leadership style and work environment that most influence on employee performance at SDN 005 Sekolaq Muliaq in West Kutai.          The problem in this research is the first; whether the style of leadership and working environment significantly influence employee performance SDN 005 Sekolaq Muliaq in West Kutai. second; whether the leadership style significantly influence employee performance SDN 005 Sekolaq Muliaq in West Kutai. Third; whether the work environment significantly influence employee performance SDN 005 Sekolaq Muliaq in West Kutai.          Basic theory used is the theory of Human Resource Management, with the hypothesis that the first hypothesis is the leadership style and working environment significantly influence employee performance, and the second hypothesis is the work environment has a more dominant influence on the performance of employees at SDN 005 Sekolaq Muliaq in West Kutai.          The analytical tool used is using classic assumption test and multiple linear regression analysis.          The result of the calculation is known that independent variables (leadership style and work environment variables) together - equally significant influence on employee performance SDN 005 Sekolaq Muliaq in West Kutai once declared first hypothesis is accepted.            It found that the variables of leadership style and working environment is partially significant effect on the performance of employees at SDN 005 Sekolaq Muliaq in West Kutai, with variable working environment more dominant influence on the performance of employees at SDN 005 Sekolaq Muliaq in West Kutai. Once declared second hypothesis is accepted.